Metode Istinbath Hukum calam Pandangan Ulama Hanafiah - Abshor, M. Ulil (CONTEMPLATE: Jurnal Ilmiah Studi Keislaman, 2022)
In doing legal decide and efforts made by Law Scholarships (read: Mujtahid) to understand text, basically not only refers to the form of pronunciation with a variety of pronunciation arrangement or it can be called the appropriate meaning of what is written, but the implicit meaning is like the sign of the meaning contained in the pronunciation and with it. In the science of Ushul Fiqih can be affirmed through Dalalah is a purpose to a certain meaning. Because Dalalah is a relationship between al-Dal and al-Madlul Al-Dal is lafazh while Al-Madlul is linguistik meaning (lughowi) Suppose al-Dal recites "prayer" while al-Madlul means prayer. Then the appointment of “Sholat” meaning in the prayer was called Dalalah. So that in the next discussion in the Hanafiah School divides into 4 types in the designation of meaning to the pronunciation, namely Nash, Ibarah Nash is a sentence instruction (Lafadz) to the desired understanding according to what is told directly by the sentence itself. Isyarah Nash is Signs and al-Nash are the designation of pronunciation of a legal provision that is not mentioned directly by the pronunciation of texts but is the norm for the meanings talked and expressed for it. Dilalah Nash is a pointer to the nash pronunciation or a legal provision also applies to something that is not mentioned because there is the existence of the ‘illat equation between the two, and Iqtida’ Nash (Muqtada al-Nash) is the designation of the nash to something that is not mentioned which is not mentioned.